Analysis of links positions in landing gear mechanism - Brewczyński, Damian; Tora, Grzegorz (Zielona Góra: Uniwersytet Zielonogórski)
This article contains a kinematic analysis of an aircraft chassis mechanism in a range of positions. The mechanism of the chassis is made up of several smaller subsystems with different functions. The first mechanism is used to eject the chassis before landing (touchdown) and fold it to hatchway after the lift off. The second mechanism is designed to perform rotation of the crossover with the wheel, in order to adjust the position of the wheel to fit it in the limited space in the hold.
Keywords: aircrafts; landing gear; mechanics; kinematics